Antibacterial and Antioxidant Activity of Green Algae Halimeda gracilis from Seribu Island District - Abdul Basir; Kustiariyah Tarman; D. Desniar (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
Seaweeds have ecological functions as primary producers in marine waters. It also has an important economic value as a producer of hydrocolloids (alginate, agar and carrageenan) that is used in various industries of food and pharmaceuticals. This study aimed to determine the antibacterial and antioxidant activity of green algae Halimeda gracilis. The study was conducted in several stages, sample collection and preparation, extraction of bioactive compound, fractionation, antibacterial and antioxidant test, and phytochemical. Extraction was done by maceration method using methanol and concentrated by rotary evaporator. The methanol extracts of H. gracilis were tested against Staphylococcus aureus and Escherichia coli. Methanol extract of H. gracilis formed inhibition zone against the test bacteria with diameter of inhibition zone was 10 mm and 6 mm, respectively. After liquid-liquid partition (water: ethyl acetate), inhibition zone was only seen in the ethyl acetate fraction of H. gracilis with diameter of inhibition zone was 6 mm and 7.50±1.71 mm, respectively. Antioxidant test methanol extracts and ethyl acetate fractions of H. gracilis each show IC50 value of 290.49 ppm and 375.50 ppm. Phytochemical test showed methanol extract of H. gracilis contains phenols and steroids.